Edible skin coating material containing neither ammonia nor morpholine - Ali, M Azhar; Zulfiqar, Adnan; Arif, Atta M (Journal of Postharvest Technology, 2017)
Ammonia and morpholine have been widely used in fruit coatings as a base to ionize fatty acids, all over the world. However, both have certain limitations now. Morpholine is banned in most countries due to its carcinogenic effects and ammonia based waxes are difficult to make owing to its high volatility. It also causes environmental hazard/irritation for the workers of the waxing factory. So an edible skin coating material without ammonia and morpholine was made in present research. The edible skin coating material was made from ethanol based microemulsion of castor oil, shellac, gum rosin and gum acacia, by atmospheric method. A new laboratory method was developed in the course to prepare an environment friendly edible skin coating material. The newly developed edible skin coating material was applied to mandarins where it successfully reduced the rate of weight loss, decrease in firmness and vitamin C, with better sensory qualities than the uncoated ones. It was also environment friendly for workers of waxing factory than the ammonia based fruit coating. The edible skin coating material was also successfully tested on cucumber and bell-pepper. It could be concluded from the results that good edible skin coating material can be made without ammonia or morpholine.